Giant Inflammatory Fibroid Polyp of the Hepatic Flexure of Colon Presenting with an Acute Abdomen - Ashish Lal Shrestha; Pradita Shrestha (Case Reports in Gastrointestinal Medicine)
Background. Inflammatory Fibroid Polyp (IFP) of the colon is an exceedingly rare condition. Since 1952 till now only 32 cases have been reported worldwide of which only 5 were giant (>4 cm) polyps mostly found in the caecum (15 cases) with only 3 in the descending colon. Case Presentation. A 36-year-old female with no previous illness presented to the emergency unit with an acute onset pain over the right hypochondrium for 3 days associated with intermittent fever and anorexia. As she had evidence of localized peritonitis she underwent a diagnostic laparoscopy and subsequently an exploratory laparotomy. A mass measuring 8 × 7 × 5 cm arising from the hepatic flexure of colon was noted. Right hemicolectomy with ileotransverse anastomosis was performed. The mass was subsequently reported to be IFP. Conclusion. IFP is a very rare condition with clinical presentation depending upon its size and location. Definitive diagnosis is possible with histopathological examination of tissue aided by immunohistochemical studies. Surgical resection has been the most common method of treatment especially for large and giant colonic IFPs owing to challenges in terms of diagnosis and technical difficulties associated with endoscopic methods.